A Girl Named Similkameen - Preece, Bronwyn (The Trumpeter, 2010)
***Please Note: I am submitting this piece as I thought it suited your search for cross-generational pieces about a connection to a place.The piece details how when I was five years old I decided that if I ever had a little girl, I would name her Similkameen. Why? Because I was overcome at such a young age by a sense of tremendous magic and awe around the headwaters of the Similkameen River in British Columbia. This feeling stayed with me, returning each time I returned to the area.In April, 2001, Similkameen Shannon O'Rourke was born.This is a Similkameen story: one that goes beyond the name, beyond the place and into the essence.